2010
DOI: 10.1073/pnas.0911482107
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-dependent endoplasmic reticulum motility and F-actin organization in plant cells

Abstract: Plants exhibit an ultimate case of the intracellular motility involving rapid organelle trafficking and continuous streaming of the endoplasmic reticulum (ER). Although it was long assumed that the ER dynamics is actomyosin-driven, the responsible myosins were not identified, and the ER streaming was not characterized quantitatively. Here we developed software to generate a detailed velocity-distribution map for the GFP-labeled ER. This map revealed that the ER in the most peripheral plane was relatively stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
379
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(412 citation statements)
references
References 43 publications
20
379
0
1
Order By: Relevance
“…These results indicated that each of the four tested myosin genes provides functionally redundant contributions to penetration resistance with myosin XI-K playing a predominant role. Interestingly, myosin XI-K also plays leading roles in transport of various organelles and in cell growth, whereas other highly expressed myosins XI provide redundant contributions to these processes (24,25). The low penetration rates of the nonadapted Bgh in Col-0 were accompanied by abortive infection with development of unilateral haustoria that were completely encased by extended papilla.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that each of the four tested myosin genes provides functionally redundant contributions to penetration resistance with myosin XI-K playing a predominant role. Interestingly, myosin XI-K also plays leading roles in transport of various organelles and in cell growth, whereas other highly expressed myosins XI provide redundant contributions to these processes (24,25). The low penetration rates of the nonadapted Bgh in Col-0 were accompanied by abortive infection with development of unilateral haustoria that were completely encased by extended papilla.…”
Section: Resultsmentioning
confidence: 99%
“…Myosins are molecular motors responsible for AF-based motility (20). Recently, plant class XI myosins were implicated in the organization of actin cytoskeleton, organelle and vesicle transport, cell expansion, and plant growth (21)(22)(23)(24)(25)(26)(27). Although none of the individual myosin gene knockouts produces plant growth defects (22), progressive elimination of two to four highly expressed myosins results in concomitant reduction in cell and plant size (23,24).…”
mentioning
confidence: 99%
“…1C). In leaf microsomes, vesicles that are positive for ER marker proteins are relatively dense and are distributed near the bottom of the gradient (Ueda et al, 2010;Zhang et al, 2010). The NAP1-positive membranes overlapped to the greatest degree with the subset of dense membranes that contained known ER marker proteins: the ER-specific GEF SEC12 and the luminal ER protein PDI (Fig.…”
Section: Nap1 Strongly Associates With Membranes and Cofractionates Wmentioning
confidence: 99%
“…in leaf epidermal cells are quite distinct (Qiu et al, 2002;Saint-Jore et al, 2002;Djakovic et al, 2006;Ueda et al, 2010). Therefore, it seemed unlikely that the general ERassociated pool of NAP1 was active in terms of localized ARP2/3 activation.…”
Section: Inactive Nap1 Is Er Localizedmentioning
confidence: 99%
“…F-actin is believed to provide tracks for intracellular trafficking events, including cytoplasmic streaming, which also is defined as the coordinated flow of cytosol that carries small organelles and vesicles (Avisar et al, 2008;Ueda et al, 2010;Bloch et al, 2016). Therefore, the disorganization of actin filaments in rmd pollen tubes prompted us to speculate that RMD may affect cytoplasmic streaming.…”
Section: Rmd Regulates the Efficiency Of Cytoplasmic Streaming In Polmentioning
confidence: 99%